2017
DOI: 10.1111/cup.12969
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic invasion predicts sentinel lymph node metastasis and adverse outcome in primary cutaneous melanoma

Abstract: The detection of LI is improved by dual immunohistochemistry and predicts SLN metastasis. The presence of LI may impact therapeutic planning in melanoma, such as the decision to perform a SLN biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
3
15
1
Order By: Relevance
“…In comparison, in our current study, we observed a strong correlation between angiotropism and lymphatic invasion. This partial discrepancy may be due, in part, to our use of a more sensitive method of detecting lymphatic invasion with S100/D240 double stains as compared to H&E analysis alone . The association of angiotropism and lymphatic invasion in this study does not necessarily suggest that there is a direct relationship between angiotropism and vascular invasion, as angiotropic foci were predominantly detected in association with CD31+ blood vessels and vascular invasion was typically identified within D240+ lymphatic vessels, and we did not observe vascular invasion in CD31+ vessels.…”
Section: Discussioncontrasting
confidence: 63%
“…In comparison, in our current study, we observed a strong correlation between angiotropism and lymphatic invasion. This partial discrepancy may be due, in part, to our use of a more sensitive method of detecting lymphatic invasion with S100/D240 double stains as compared to H&E analysis alone . The association of angiotropism and lymphatic invasion in this study does not necessarily suggest that there is a direct relationship between angiotropism and vascular invasion, as angiotropic foci were predominantly detected in association with CD31+ blood vessels and vascular invasion was typically identified within D240+ lymphatic vessels, and we did not observe vascular invasion in CD31+ vessels.…”
Section: Discussioncontrasting
confidence: 63%
“…In our recent analysis of melanomas from patients who underwent SLN biopsy, we found the sensitivity and specificity of predicting SLN metastasis with lymphatic invasion on dual S100/D2-40 IHC were 44% and 82%, respectively. 32 In addition, patients without lymphatic invasion were more likely to be disease free at last follow-up (79%) than patients with lymphatic invasion (54%) detected on S100/D2-40 IHC (average followup = 22 months and 24 months, respectively).…”
Section: Lymphatic Invasion and Metastasismentioning
confidence: 92%
“…We recently studied 105 melanomas with dual S100/D2-40 IHC and detected lymphatic invasion in 23%. 32 Unequivocal lymphatic invasion can be recognized when S100-positive cytologically atypical cells, stained with a red chromogen, are seen circumferentially surrounded by a thin D2-40-positive lymphatic endothelium, stained with a brown chromogen. Either solid tumor emboli or single tumor cells may be seen within the lymphatic spaces.…”
mentioning
confidence: 99%
“…The present study has several limitations. Lymphatic invasion is a known prognostic factor in melanoma, but could unfortunately not be assessed reliably in this study because there were too many missing values (30·3 per cent). The retrospective design and short follow‐up of some patients are other limitations.…”
Section: Discussionmentioning
confidence: 96%